Protective Malaria Vaccine in Mice Based on the Plasmodium vivax Circumsporozoite Protein Fused with the Mumps Nucleocapsid Protein - Marques, Rodolfo F. (Vaccines (Basel), 2020)
Plasmodium vivax is the most common species of human malaria parasite found outside Africa, with high endemicity in Asia, Central and South America, and Oceania. Although Plasmodium falciparum causes the majority of deaths, P. vivax can lead to severe malaria and result in significant morbidity and mortality. The development of a protective vaccine will be a major step toward malaria elimination. Recently, a formulation containing the three allelic variants of the P. vivax circumsporozoite protein (PvCSP—All epitopes) showed partial protection in mice after a challenge with the hybrid Plasmodium berghei (Pb) sporozoite, in which the PbCSP central repeats were replaced by the VK210 PvCSP repeats (Pb/Pv sporozoite). In the present study, the chimeric PvCSP allelic variants (VK210, VK247, and P. vivax-like) were fused with the mumps virus nucleocapsid protein in the absence (NLP-CSP(R)) or presence of the conserved C-terminal (CT) domain of PvCSP (NLP-CSP(CT)). To elicit stronger humoral and cellular responses, Pichia pastoris yeast was used to assemble them as nucleocapsid-like particles (NLPs). Mice were immunized with each recombinant protein adjuvanted with Poly (I:C) and presented a high frequency of antigen-specific antibody-secreting cells (ASCs) on days 5 and 30, respectively, in the spleen and bone marrow. Moreover, high IgG titers against all PvCSP variants were detected in the sera. Later, these immunized mice with NLP-CSP(CT) were challenged with Pb/Pv sporozoites. Sterile protection was observed in 30% of the challenged mice. Therefore, this vaccine formulation use has the potential to be a good candidate for the development of a universal vaccine against P. vivax malaria.